2018
DOI: 10.1007/s13193-018-0744-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Pancreaticoduodenectomy at Low-Volume Centre in Tier-II City of India

Abstract: Currently, pancreaticoduodenectomy (PD) is considered a common and feasibly performed surgery for periampullary tumours, but it is still a high-risk surgical procedure with potential morbidity and mortality rates. Previously, it was emphasised for the need of high-volume centres to perform specialised surgery such as PD. The authors have made an attempt to know the relation between low-volume centre and outcomes of PD. The study was conducted in a Tier-II city referral hospital located in Karnataka, India. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 31 publications
1
14
0
2
Order By: Relevance
“…The reported postoperative fistula rates at three other centers from India were 15%, 15.39%, and 12% respectively, 24–26 and the fistula rate at our center was 17.0%. Studies have shown that high volume centers and high volume surgeons provide best outcomes after pancreaticoduodenectomy 25,27,28 . Pancreaticoduodenectomy is associated with major postoperative complications.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…The reported postoperative fistula rates at three other centers from India were 15%, 15.39%, and 12% respectively, 24–26 and the fistula rate at our center was 17.0%. Studies have shown that high volume centers and high volume surgeons provide best outcomes after pancreaticoduodenectomy 25,27,28 . Pancreaticoduodenectomy is associated with major postoperative complications.…”
Section: Discussionmentioning
confidence: 44%
“…At high volume centers, apart from availability of enough resources, they are usually equipped with experienced team (critical care team, intervention radiologists, experienced surgeons, and nursing staff), which can improve postoperative outcomes of patients by timely identification and intervention for management of these complications 29 . A study from India has shown that even at low volume centers, outcomes of patients after pancreatic surgery are minimally affected if hospital is equipped with better infrastructure and experienced team who can manage postoperative complications 25 . We consider our institute in a transition phase from low volume to high volume center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles found in this research 11,13,15,18 highlighted the importance of chlorhexidine bath in patients with potentially contaminated surgeries for the prevention of SSI. It is recommended that the bath should be performed with soap and water, the night before or the morning of surgery 3,28 ; there is no consensus on the indication of the use of antiseptic for all surgeries, however, its use is indicated in large surgeries, with implants or in cases of outbreaks of infection in surgeries. Trichotomy should be performed only when necessary, immediately before the surgical procedure, without the use of blades, prioritizing the use of electric tricotomizers, trimmers or scissors 11,19 , being in accordance with the Healthcare related infection prevention measures established by the Brazilian Ministry of Health 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative nursing interventions are associated with surgical environment 15,18,19 , surgical antisepsis of the hands with degermating antiseptic or alcohol-based product 15,19, potential for contamination of operative wound 18,19 , surgical duration 19 and sterile glove replacement 15 . These interventions were also recommended in national 1,8 and international original articles 28 , national 29 and international systematic reviews 30 , and in the recommendations established by the Centers for Disease Control and Prevention (CDC) 31 .…”
Section: Discussionmentioning
confidence: 99%